Ergenlerde Sıkıntı-Östres Ölçeği’nin Türkçe’ye Uyarlanması - EKŞİ, HALİL (My University, 2021)
Amaç: Bu çalışmanın amacı Branson, Dry, Palmer ve Turnbull tarafından geliştirilen Ergenlerde Sıkıntı Östres Ölçeği’nin (ESÖÖ) geçerlik vegüvenirlik gibi psikometrik özelliklerini incelemek ve Türkçe'ye uyarlama çalışmalarını gerçekleştirmektir.Gereç ve Yöntem: Araştırmaya 2019-2020 eğitim öğretim yılında İstanbul Tuzla ilçesinde farklı resmi ortaöğretim kurumlarında eğitimgören 261 kadın ve 105 erkek olmak üzere toplam 366 lise öğrencisi katılım göstermiştir. Ölçeğin Türkçe versiyonunun psikometrik özellikleriniincelemek için dilsel eş değerlik, ölçüt uyum geçerliği, iç tutarlılık katsayısının hesaplanması ve doğrulayıcı faktör analizi yapılmıştır.Bulgular: Ölçeğin yapı geçerliği doğrulayıcı faktör analizi ile incelenmiş ve Ergenlerde Sıkıntı Östres Ölçeği’nin alt boyutlarını oluşturanikili yapı doğrulanmıştır. Ölçüt uyum geçerliği çalışması sonucunda ESÖÖ- Sıkıntı alt boyutu ile Genel Öz Yeterlik Ölçeği arasında negatif,Algılanan Stres Ölçeği arasında pozitif yönlü anlamlı ilişkiler bulunmuştur. ESÖÖ-Östres alt boyutu ile Genel Öz Yeterlik Ölçeği arasındapozitif, Algılanan Stres Ölçeği arasında negatif yönlü anlamlı ilişkiler bulunmuştur. İç tutarlık analizi sonucunda güvenilirlik Cronbach alphakatsayısı ESÖÖ-Sıkıntı alt boyutu için .81, ESÖÖ-Östres alt boyutu için ise .84 olarak hesaplanmıştır.Sonuç: Araştırma bulgularından hareketle Ergenlerde Sıkıntı-Östres Ölçeği Türkçe Formu’nun geçerli ve güvenilir bir ölçme aracı olduğuortaya konmuştur.

Objectives: The aim of this study is to analyze the psychometric properties of Adolescent Distress Eustress Scale developed by Branson, Dry,_x000D_ Palmer and Turnbull, such as validity and reliability, and to carry out adaptation studies to Turkish._x000D_ Materials and Methods: In the 2019-2020 academic year, a total of 366 high school students, 261 female and 105 male, studying at_x000D_ different official secondary schools in Tuzla, Istanbul, participated in the study. In order to examine the psychometric properties of the Turkish_x000D_ version of the scale, linguistic equivalence, criterion concordance validity, calculation of internal consistency coefficient and confirmatory_x000D_ factor analysis were performed._x000D_ Results: The construct validity of the scale was examined by confirmatory factor analysis and the dual structure, which constituted the subdimensions of the Adolescent Boredom Estress scale (ADES), was confirmed. As a result of the criterion compliance validity study, negative_x000D_ correlations were found between the ADES-Distress sub-dimension and the General Self-Efficacy scale and positively significant correlations_x000D_ were found with the Perceived Stress Scale. Positive significant relationships were detected between ADES-Eustress sub-dimension and General_x000D_ Self-Efficacy scale, and negative significant relationships were found with the Perceived Stress Scale. As a result of the internal consistency_x000D_ analysis, the reliability Cronbach alpha coefficient was calculated as .81 for the ADES-Distress sub-dimension and .84 for the ADES-Eustress_x000D_ sub-dimension._x000D_ Conclusion: Based on the findings of the research, it has been revealed that the Turkish version of the Adolescent Distress Eustress Scale is_x000D_ a valid and reliable measurement tool.
Adaptation of Adolescent Distress-Eustress Scale into Turkish